Evaluasi Pemeriksaan Kreatinin dengan Penundaan 12 Jam pada Pasien Diabetes Melitus - Kesuma, suryanata; Eka Farpina, Eka Farpina; Sultan, Sultan (Jurnal Sains & Kesehatan, 2024)
Clinical laboratories must always pay attention to the quality of service and quality of examination. The clinical laboratory will provide information in the form of examination results to clinicians so that they can be used to make a diagnosis and follow up treatment of patients. Clinicians always expect the results of the examination to be precise and accurate according to the patient's condition at that time. Examination results and precise measurements can minimize errors in determining the diagnosis of the patient's disease at that time. The purpose of this study was to find out the clinical differences in delaying immediate and delayed 12-hour creatinine checks in patients with diabetes mellitus. The type of research used in this research is descriptive, the specimens used are serum, the data collection technique uses primary data, Mindray Chemistry Analyzers BS240, data processing in this study uses MicrosoftExcel. The results of this study showed an average of 0.9 mg/dL on immediate examination and a 12-hour delay of 0.6 mg/dL. The accuracy (d%) of the immediate creatinine check against a 12-hour delay was -24.8%. Precision (CV%) on immediate creatinine examination against a 12-hour delay of 20.0% andtotalerror on immediate creatinine examination against a 12- hour delay of 64.8%. Based on these results indicate that there are differences   in   clinical   results   in   the   immediate   creatinine examination and a delay of 12 hours.